Pelanggaran Etika Pariwara Indonesia pada Iklan Pembesar Kelamin Prostanore di Platform Digital - Sheilla Ekawati; Farrel Aditya; Muhammad Fawwaz Fauzarrahman; Fajar Junaedi (ANALOGI Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the violations of the Indonesian Advertising Ethics in the advertisement of the Prostanore male enhancement product, which has raised concerns due to its potential impact on society. Utilizing a descriptive qualitative method and a postpositivist paradigm, this research collected data through documentation and literature review, and analyzed the advertisement found on digital platforms. The findings indicate that the Prostanore advertisement violates several provisions of the Indonesian Advertising Ethics, including airing on media not suitable for an adult demographic and making exaggerated claims about the product's efficacy. Additionally, the use of misleading terms such as "side effect-free" was also identified as a violation. The conclusion of this study emphasizes the need for stricter oversight of advertisements that may harm consumers and the importance of educating advertisers about ethical advertising practices. This research is expected to encourage advertisers to be more responsible in conveying accurate and ethical information, thereby creating a healthier advertising environment.